American dirt: a novel (Macmillan Audio, Flatiron Books, 2020)
"También de este lado hay sueños. On this side, too, there are dreams... Lydia Quixano Perez lives in the Mexican city of Acapulco. She runs a bookstore. She has a son, Luca, the love of her life, and a wonderful husband who is a journalist. And while there are cracks beginning to show in Acapulco because of the drug cartels, her life is, by and large, fairly comfortable. Even though she knows they'll never sell, Lydia stocks some of her all-time favorite books in her store. And then one day a man enters the shop to browse and comes up to the register with four books he would like to buy -- two of them her favorites. Javier is erudite. He is charming. And, unbeknownst to Lydia, he is the jefe of the newest drug cartel that has gruesomely taken over the city. When Lydia's husband's tell-all profile of Javier is published, none of their lives will ever be the same. Forced to flee, Lydia and eight-year-old Luca soon find themselves miles and worlds away from their comfortable middle-class existence. Instantly transformed into migrants, Lydia and Luca ride la bestia -- trains that make their way north toward the United States, which is the only place Javier's reach doesn't extend. As they join the countless people trying to reach el norte, Lydia soon sees that everyone is running from something. But what exactly are they running to? AMERICAN DIRT will leave readers utterly changed when they finish reading it. A page-turner filled with poignancy, drama, and humanity on every page, it is a literary achievement." -- Publisher's description.

Against all enemies (A Campus Novel, ,, 2011)
For years, ex-Navy SEAL Maxwell Moore has worked across the Middle East and behind the scenes for the Special Activities Division of the CIA, making connections, extracting valuable intelligence, and facing off against America's enemies at every turn. When Moore arrives at a rendezvous to take charge of a high-ranking Taliban captive, the meeting takes a horrific turn.

Santa Fe dead ([Ed Eagle, 3,, 2008)
Attorney Ed Eagle thinks he's safe from his black widow ex-wife, who is now in police custody. But when she escapes, she spins a new web that just might trap him'and everyone he loves.

Mexican Gothic (Del Rey, Random House Worlds, Books on Tape, 2020)
"The acclaimed author of Gods of Jade and Shadow comes this reimagining of the classic gothic suspense novel, a story about an isolated mansion in 1950s Mexico -- and the brave socialite who's drawn to its treacherous secrets." -- Dust jacket flap.

The Mayan secrets (Fargo adventures, 5,, 2013)
Husband-and-wife team Sam and Remi Fargo are in Mexico, when they come upon a remarkable discovery: the skeleton of a man clutching an ancient sealed pot, and within the pot, a Mayan book, larger than anyone has ever seen. The book contains astonishing information about the Mayans, about their cities, and about mankind itself. The secrets are so powerful that some people would do anything to possess them -- as the Fargos are about to find out.

The daughter of Doctor Moreau: a novel (Del Rey, Random House Worlds, Books on Tape, 2022)
"From the bestselling author of Mexican Gothic and Velvet Was the Night comes a dreamy reimagining of The Island of Doctor Moreau set against the backdrop of nineteenth-century Mexico. Carlota Moreau: A young woman growing up on a distant and luxuriant estate, safe from the conflict and strife of the Yucatan peninsula. The only daughter of a researcher who is either a genius or a madman. Montgomery Laughton: A melancholic overseer with a tragic past and a propensity for alcohol. An outcast who assists Dr. Moreau with his experiments, which are financed by the Lizaldes, owners of magnificent haciendas and plentiful coffers. The hybrids: The fruits of the doctor's labor, destined to blindly obey their creator and remain in the shadows. A motley group of part human, part animal monstrosities. All of them live in a perfectly balanced and static world, which is jolted by the abrupt arrival of Eduardo Lizalde, the charming and careless son of Dr. Moreau's patron, who will unwittingly begin a dangerous chain reaction. For Moreau keeps secrets, Carlota has questions, and, in the sweltering heat of the jungle, passions may ignite. The Daughter of Doctor Moreau is both a dazzling historical novel and a daring science fiction journey"--Dust jacket flap.

Cities of the plain (Border trilogy, 3,, 1998)
In this final volume of The Border Trilogy, two men marked by the boyhood adventures of All the Pretty Horses and The Crossing now stand together, in the still point between their vivid pasts and uncertain futures, to confront a country changing or already changed beyond recognition. In the fall of 1952, John Grady Cole and Billy Parham—nine years apart in age, yet with a kinship greater than perhaps they know—are cowboys on a New Mexico ranch encroached upon from the north, at Alamogordo, by the military. To the south, always on the horizon are the mountains of Mexico, looming over El Paso, Ciudad Juárez and all the cities of the plain. Bound by nature to horses and cattle and range, these two discover that ranchlife domesticity is compromised, for them and the men they work with, by a geometry of loss afflicting old and young alike, those who have survived it and anyone about to try. And what draws one of them across the border again and again, what would bind "those disparate but fragile worlds," is a girl seized by ill fortune, and a love as dangerous as it is inevitable. This story of friendship and passion is enfolded in a narrative replete with character and place and event—a blind musician, a marauding pack of dogs, curio shops and ancient petroglyphs, a precocious shoe-shine boy, trail drives from the century before, midnight on the highway—and with landforms and wildlife and horses and men, most of all men and the women they love and mourn, men and their persistence and memories and dreams. With the terrible beauty of Cities of the Plain—with its magisterial prose, humor both wry and out-right, fierce conviction and unwavering humanity—Cormac McCarthy has completed a landmark of our literature and times, an epic that reaches from tales of the old west, the world past, into the new millennium, the world to come. Look for Cormac McCarthy's latest novels, The Passenger and Stella Maris.

Silver nitrate (Del Rey, Random House Worlds, Books on Tape, 2023)
"Montserrat has always been overlooked. She's a talented sound editor, but she's left out of the boys' club running the film industry in '90s Mexico City. And she's all but invisible to her best friend, Tristan, a charming if faded soap opera star, though she's been in love with him since childhood. Then Tristan discovers his new neighbor is the cult horror director Abel Urueta, and the legendary auteur claims he can change their lives--even if his tale of a Nazi occultist imbuing magic into highly volatile silver nitrate stock sounds like sheer fantasy. The magic film was never finished, which is why, Urueta swears, his career vanished overnight. He is cursed. Now the director wants Montserrat and Tristan to help him shoot the missing scene and lift the curse . . . but Montserrat soon notices a dark presence following her, and Tristan begins seeing the ghost of his ex-girlfriend. As they work together to unravel the mystery of the film and the obscure occultist who once roamed their city, Montserrat and Tristan may find that sorcerers and magic are not only the stuff of movies."--

The Sooner the Better (Deliverance Company, ,, 2010)
Lorraine Dancy has just discovered that everything she believes about her father is a lie--starting with the fact that Thomas supposedly died years ago. Now she's learned that not only is he not dead, he's living in a small town south of the border. In the process of tracking him down, she manages to get framed for theft and pursued by the real thief, the police and a local crime boss. Her father's friend Jack Keller agrees to help her escape, although Lorraine's reluctant to depend on a man like him. Jack's every bit the renegade Lorraine thinks he is--an ex-mercenary and former Deliverance Company operative. He's also the one person who can guide her to safety. But there are stormy waters ahead, including an attraction neither of them wants to feel. An attraction that's as risky as it is intense--for both of them. The sooner he can get Lorraine home, the better!

Untamed shore (Polis Books, Agora Books, an imprint of Polis Books, LLC, 2020)
A coming-of-age story set in Mexico which quickly turns dark when a young woman meets three enigmatic tourists. Baja California, 1979. Viridiana spends her days watching the dead sharks piled beside the seashore, as the fishermen pull their nets. There is nothing else to do, nothing else to watch, under the harsh sun. She's bored. Terribly bored. Yet her head is filled with dreams of Hollywood films, of romance, of a future beyond the drab town where her only option is to marry and have children. Three wealthy American tourists arrive for the summer, and Viridiana is magnetized. She immediately becomes entwined in the glamorous foreigners' lives. They offer excitement, and perhaps an escape from the promise of a humdrum future. When one of them dies, Viridiana lies to protect her friends. Soon enough, someone's asking questions, and Viridiana has some of her own about the identity of her new acquaintances. Sharks may be dangerous, but there are worse predators nearby, ready to devour a naive young woman who is quickly being tangled in a web of deceit.

The crossing (Border Trilogy, ,, 1994)
NATIONAL BESTSELLER • The second volume of the award-winning Border Trilogy—From the bestselling author of The Passenger and the Pulitzer Prize–winning novel The Road—fulfills the promise of All the Pretty Horses and at the same time give us a work that is darker and more visionary, a novel with the unstoppable momentum of a classic western and the elegaic power of a lost American myth. In the late 1930s, sixteen-year-old Billy Parham captures a she-wolf that has been marauding his family's ranch.  But instead of killing it, he decides to take it back to the mountains of Mexico.  With that crossing, he begins an arduous and often dreamlike journey into a country where men meet ghosts and violence strikes as suddenly as heat-lightning—a world where there is no order "save that which death has put there." An essential novel by any measure, The Crossing is luminous and appalling, a book that touches, stops, and starts the heart and mind at once. Look for Cormac McCarthy's latest bestselling novels, The Passenger and Stella Maris.

Trinity sight: a novel (Blackstone Publishing, 2019)
"Anthropologist Calliope Santiago awakens to find herself in a strange and sinister wasteland, a shadow of the New Mexico she knew. Empty vehicles litter the road. Everyone has disappeared--or almost everyone. Calliope, heavy-bellied with the twins she carries inside her, must make her way across this dangerous landscape with a group of fellow survivors--"--from book jacket.